A gestão do conhecimento e sua relação com desempenho organizacional em empresas industriais de médio porte - Sabadin, Marcilde (2017)
The theme of this Masters Dissertation, knowledge management (GC), is researched with a view to understanding how the CG can contribute to the performance of the industrial companies. In this context, some authors have been focusing on studies for the bestunderstanding of how the KM occurs, translating its practice into dimensions, indicators, actions, facilitators and limiters, which include perceptible results, both financial as non-financial, since only Organizational Development is possible (OD) when people are willing to learn.The theme in vogue in this Master's work, knowledge management (GC) has itsorigins in Karl Wiig. Activities involving artificial intelligence led him to studyGC. In the late 1980s, the focus shifted from technology to mankind and, according towith Cianconi (2003), Karl Wiig was one of the first to use this term, focusing on artificial intelligence applied to business.